#TITLE_ALTERNATIVE# - Haryono ( NIM: 20105017), Mohamad
Abstract; In analysis of phylogenetic model, intensity of nucleotide substitution is very important as a measure of evolutionary rate. Hidden Markov model (HMM) is allowed in this model for category of evolutionary rate, by assuming that rate of evolution is different for each site. In here, evolutionary rate is assumed having gamma distribution. Felsenstein Algorithm is used to calculate likelihood of the model. This algorithm is identical process with backward algorithm that usually used in HMM. Viterbi algorithm is used to find the optimal state of rate category. To estimate transition matrix, we used Baum Welch algorithm by involving autocorrelation function from rate categories among neighboring sites.